Dissimilar friction stir lap welding of AA 5754-H22/AA 6082-T6 aluminium alloys: Influence of material properties and tool geometry on weld strength. (15th December 2015) - Costa, M.I.; Verdera, D.; Leitão, C.; Rodrigues, D.M.
Abstract: Dissimilar friction stir welding (FSW) of heat (AA 6082-T6) and non-heat (AA 5754-H22) treatable aluminium alloys, in lap joint configuration, was performed in this work. The base material plates were 1 mm thick. Welds were performed combining different plates positioning, relative to the tool shoulder, in order to assess the influence of base materials properties on welds strength. Three different tools were tested, one cylindrical and two conical, with different taper angles. Welds strength was characterized by performing transverse and tensile–shear tests. Strain data acquisition by Digital Image Correlation (DIC) was used to determine local weld properties. The results obtained enabled to conclude that the dissimilar welds strength is strongly dependent on the presence of the well-known hooking defect and that the hooking characteristics are strongly conditioned by base materials properties/positioning. By placing the AA 6082-T6 alloy, as top plate, in contact with the tool shoulder, superior weld properties are achieved independently of the tool geometry. It is also concluded that the use of unthreaded conical pin tools, with a low shoulder/pin diameter relation, is the most suitable solution for the production of welds with similar strengths for advancing and retreating sides. Graphical abstract: Highlights: The hooking defect determines the weld strength. The hook formation depends on tool geometry and base material positioning. Dissimilar base material combination influences the material flow during welding. Strongest welds are produced by placing the AA 6xxx alloy in the top. Conical tools with low shoulder/pin diameters ratio hinder hooking formation.